A view to the origin, evolution and development of the Faculty of Physical Culture «Nancy Uranga Romagoza at the University of Pinar del Rio "Hermanos Saíz Montes de Oca" - María Ofelia Armas Álvarez; René Mesa Peña; María Victoria Hernández Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
This work is the outcome of a systematic work coming from people who have saved deep and experienced records about the Faculty of Physical Culture"Nancy Uranga Romagoza", University of Pinar del Río "Hermanos Saíz Montes de Oca", Cuba. Throughout this article you can find the process of establishment and evolution of the Sport Faculty of Physical Culture "Nancy Uranga Romagoza" in Pinar del Río, taking in to consideration the critics and opinions of experts. The objective of the research is to preserve the historical background of the Faculty of Physical Culture "Nancy Uranga Romagoza" and the show the compiled work to the present and future generations. In this way it can be reinforced the sense of identity and positive moral values in the institution. To carry out this study it was necessary to apply some interviews and to consult some documents about the constitution of the Faculty of Physical Culture "Nancy Uranga Romagoza" attending to the different stages of evolution.